The Environmental Pollutant Cadmium Promotes Influenza Virus Replication in MDCK Cells by Altering Their Redox State - Checconi, Paola (MDPI, 2013)
Cadmium (Cd) is a toxic heavy metal that is considered an environmental contaminant. Several sources of human exposure to Cd, including employment in primary metal industries, production of certain batteries, foods, soil and cigarette smoke, are known. Its inhalation has been related to different respiratory diseases and toxic effects, among which alterations of the physiological redox state in individuals exposed to the metal have been described. Host-cell redox changes characteristic of oxidative stress facilitate the progression of viral infection through different mechanisms. In this paper, we have demonstrated that pre-treatment with CdCl(2) of MDCK cells increased influenza virus replication in a dose-dependent manner. This phenomenon was related to increased viral protein expression (about 40% compared with untreated cells). The concentration of CdCl(2), able to raise the virus titer, also induced oxidative stress. The addition of two antioxidants, a glutathione (GSH) derivative or the GSH precursor, N-acetyl-l-cysteine, to Cd pre-treated and infected cells restored the intracellular redox state and significantly inhibited viral replication. In conclusion, our data demonstrate that Cd-induced oxidative stress directly increases the ability of influenza virus to replicate in the host-cell, thus suggesting that exposure to heavy metals, such as this, could be a risk factor for individuals exposed to a greater extent to the contaminant, resulting in increased severity of virus-induced respiratory diseases.